'I see fire and I see rain'. Notes on the state museum reform in Italy. (2nd November 2018) - Curioni, Stefano Baia
ABSTRACT: From 2014 to 2017 public museums in Italy went into a strong phase of change due to the reform enacted by the Minister of Culture. The reform, both as whole and in terms of each individual measure contained in it, has come in for strong criticism and opposition sparked by a broad range of technical, political, ideological and empirical considerations. The complexity of the stances adopted and the multi-faceted nature of the critical response make it very difficult today to offer a consistent and complete picture of events. Not much time has gone by and many processes are still in the embryonic stage, so it is not even methodologically legitimate to form a stable overview of its impact today. In this essay, we attempt a reconstruction of the way things have developed to date, highlighting a number of issues that have emerged in connection with certain processes triggered by the reform, with respect to long unresolved broad problems that encompass the entire evolution of the civil functions of the Ministry of Culture in Italy.